18F-FLOURODEOXYGLUCOSE (18FDG) POSITRON-EMISSION TOMOGRAPHY (PET) AS IMAGING MODALITIES ON THYROID CANCER MANAGEMENT - Ary Wismayana, I Putu; Dwi Martadiani, Elysanti; Astuti, Lisna (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Thyroid cancer prevalence tend to increase, by 2008 there are 37.340 cases with mortality rate reached 1.590. Traditionally USG and scintigraphy are major imaging modality to diagnose or predict the prognosis of thyroid cancer. On special case, ultrasonography or scintigraphy cannot be use due to anatomical change after surgical procedure or low iodine uptake. Positron-Emission Tomography (PET) is noninvasive, three-dimensional, nuclear imaging technique. PET can evaluate both anatomical and functional. 18 F-Flourodeoxyglucose PET can evaluate function and abnormality of thyroid which cannot be evaluated using another imaging modalities. PET can detect papillary and follicular thyroid cancer relaps with negative increasing thyroglobuline and radioiodine scanning negative, instead of detects medularry thyroid cancer earlier. Benefits of PET limited due to cost and technology.
Keywords: Positron-Emission Tomography (PET), thyroid cancer